Tuning the structure of cerium phosphate nanorods. Issue 46 (10th November 2021) - Allen, Lisa; Davies-Jones, Josh A.; Davies, Philip R.; King, Sarah; O'Reilly, Padraic
Abstract : The one-pot, shape selective synthesis of cerium phosphate nanorods has been explored and developed to give nanoparticles with aspect ratios between 3–24.8. Abstract : The one-pot, shape selective synthesis of cerium phosphate nanorods has been explored and developed to give nanoparticles with aspect ratios between 3–24.8. Studies of the surface with photo induced force microscopy show for the first time that despite the hexagonal phase bulk structure, mixed monoclinic and hexagonal domains are present in the surface layer demonstrating the importance of surface sensitive, nanoscale vibrational spectroscopy in nanoparticle science. There is also evidence that carbonate is adsorbed preferentially on the monoclinic domains, though whether the carbonate is the cause of the domains or merely adsorbs more easily on this structure has not been determined. Co, Ni and Mn-doped cerium phosphate rods were prepared successfully with aspect ratios of >20. The introduction of dopant ions has a measurable effect upon the magnetic susceptibility but a more significant effect on the bulk crystal phase of the nanoparticles, introducing up to ∼30% monoclinic phosphate in the doped rods.